From tradition to innovation: implementation of the Library of Things at Cesmac University Center (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
This study aims to analyze the implementation process of the Library of Things in the CESMAC University Center Library Network, as well as to assess its relevance and impact on the academic community. Using case study methodology, this research is characterized as exploratory and descriptive. The results indicate that the incorporation of twelve items into the Library of Things collection accounted for 43% of total annual loans, demonstrating the effectiveness and ease of use of this innovation for the academic community.
Keywords: library of things; sustainability; university library